La contabilidad gubernamental y la herramienta de gestión presupuestaria en la Municipalidad Distrital de Punchana año 2022 - Hauxwell Saavedra, Gardenia (2025)
The accounting postulates evaluate the economic and accounting activities that lead to a sufficiently good balance of government accounting. The current public accountant thesis carries out research to determine the relationship between government accounting and the budget management tool in the district municipality of Punchana in 2022. For this purpose, this Quantitative type research was carried out, Correlational level and Non-Experimental design. The research concludes efficiently and directly relates between government accounting and the budget management tool in the district municipality of Punchana in 2022, demonstrated with the Correlation Coefficient r = 0.421; and the Bilateral Significance = 0.013 obtained in table 18. Likewise, it has been proven that in specific hypothesis 1, the basic postulates determine the behavior of Government Accounting in the District Municipality of Punchana Year 2022, having obtained a Coefficient of Correlation r = 0.521; and the Bilateral Significance = 0.004 obtained in table 19. On the other hand, it has been proven that in specific hypothesis 2, systematic registration is the greatest concept in the technical standards and procedures in the District Municipality of Punchana Year 2022, having obtained a Correlation Coefficient r = 0.709; and the Bilateral Significance = 0.038 obtained in table 20. Finally, it has been proven that in specific hypothesis 3, Budget Management has an increasing behavior in the District Municipality of Punchana Year 2022, having obtained a Correlation Coefficient r = 0.189; and the Bilateral Significance = 0.017 obtained in table 21.